PEDAGOGICAL CONDITIONS FOR DEVELOPING CREATIVE THINKING IN TEACHING TECHNOLOGY. (Universal International Scientific Journal, 2026)
This article discusses the content and essence of developing the creativity of future technology teachers. It also analyzes the sharp increase in the volume of scientific knowledge, concepts and imagination as a result of the rapid development of science and technology. In such conditions, the growing demand for future technology teachers with creative potential and the need to form their professional competence at a high level are justified.
Keywords: science, technique, creativity, technology, professional competence, innovation, knowledge, skills, qualifications, idea, imagination, strategy, specialist, education system, methodology.